Spare Parts Inventory Optimization for Military Vehicles Using a Mixed Probability Distribution - Mojtaba Salehi; Mojtaba Omidvar; Shohreh Shariati (پژوهش در مدیریت تولید و عملیات)
Purpose: In general, inventory optimization is one of the most important techniques in the production system, because the high cost of an empty warehouse and the cost of losing customers can cause serious damage to a system. The basic idea for inventory is to provide flexibility for a system and protect the system against events such as stock out. Inventory capacity for each product or part is defined by demand, delivery time and part price. By balancing the supply and demand rates, the optimal inventory capacity can be achieved. It is necessary to use practical and effective techniques and solutions to reduce breakdowns to optimally use existing equipment and resources and reduce large costs in terms of energy wastage and repairs and repurchase of equipment. In this context, spare parts are one of the most important links in performing optimal maintenance and repairs and quickly returning equipment to the production line. In good management of spare parts, the inventory system of the warehouse will lead to the reduction of maintenance and repair costs, manpower and the duration of equipment failure and will ultimately help to increase productivity. This study aims to optimize the inventory level of spare parts for military vehicles using a mixed probability distribution. Design/methodology/approach: First, based on the literature review and selected basic articles, the research gaps have been identified, and accordingly, a mathematical model has been developed and solved to optimize the spare parts of military vehicles. Then, a meta-inventive method has been used to solve the problem. This is because the use of meta-heuristic methods to check and analyze the sensitivity of inventory optimization models can lead to better and more accurate results, and also the use of these methods is relatively new and helps in solving optimization problems. Also, the problem studied in this research is a non-linear integer programming model, which has been used for the problems of medium and large dimensions due to the complexity of the problem. The meta-heuristic method based on the genetic algorithm has been applied to save the total costs. Finally, to prove the effectiveness of the model, the proposed model has been implemented in a case study on the parts of military vehicles in the 177th Brigade of Torbet Heydarieh. Findings: Findings indicated that the optimal system cost value and the economic order value were obtained during specific iterations of the model, i.e., the first, fourth, and tenth iterations. These points implied the effectiveness of integrating Poisson and Exponential distributions in the model and optimizing the system performance in different scenarios. Such results emphasize the consistency and robustness of the proposed inventory management strategy, especially when demand fluctuates and supply challenges. As the model is subjected to more iterations, differences in results are observed, indicating the potential for variability with increasing iterations. For example, if the model considers 100 different problems or scenarios, different results may appear, although a general consistency in system behaviour is noted. This indicates flexibility in the modelling approach, where even significant changes in parameters such as inventory costs or lead times are unlikely to drastically change the economic value or efficiency of the system. Research limitations: This research was conducted on a case-by-case basis on the parts of military vehicles of the 177th brigade of Torbat Heydarieh city, so it should be possible to generalize it to other organizations, and because it was typically a cross-sectional study, conclusions about on the causality might seem difficult. Practical implications: The main challenge in the supply chain is to control inventory levels by determining the size of orders for each department during each period to optimize the objective function, which has been investigated in various studies because inventory optimization is one of the important and practical techniques for optimizing the economic value of the order and realizing a stable situation in a production system. This is particularly important since the high cost of an empty warehouse and the cost of losing customers can cause serious damage to a system Social implications - Due to the specific conditions of embargo and restrictions on access to international markets, accurate inventory management can serve as a key tool to maintain efficiency and sustainability in military operations. This research recommends that relevant organizations continuously analyze and optimize their inventory levels using mathematical models and optimization algorithms such as genetic algorithms to avoid additional costs and at the same time, to ensure the supply of parts in times of need. Originality/value: Predicting exactly what and how many spare parts are needed for the necessary equipment in a business and when they are needed to be available in its warehouse is an important issue to consider. These parts are identified and managed to support the functions of critical equipment, and the lack of critical spare parts during planned or unplanned repairs will significantly influence the overall effectiveness of the equipment.